Mindfulness‐Based Stress Reduction in Women with Overweight or Obesity: A Randomized Clinical Trial. Issue 8 (7th July 2017) - Raja‐Khan, Nazia; Agito, Katrina; Shah, Julie; Stetter, Christy M.; Gustafson, Theresa S.; Socolow, Holly; Kunselman, Allen R.; Reibel, Diane K.; Legro, Richard S.
Abstract : Objective: To evaluate the feasibility and cardiometabolic effects of mindfulness‐based stress reduction (MBSR) in women with overweight or obesity. Methods: Eighty‐six women with BMI ≥ 25 kg/m 2 were randomized to 8 weeks of MBSR or health education and followed for 16 weeks. The primary outcome was the Toronto Mindfulness Scale. Secondary outcomes included the Perceived Stress Scale‐10, fasting glucose, and blood pressure. Results: Compared to health education, the MBSR group demonstrated significantly improved mindfulness at 8 weeks (mean change from baseline, 4.5 vs. −1.0; P = 0.03) and significantly decreased perceived stress at 16 weeks (−3.6 vs. −1.3, P = 0.01). In the MBSR group, there were significant reductions in fasting glucose at 8 weeks (−8.9 mg/dL, P = 0.02) and at 16 weeks (−9.3 mg/dL, P = 0.02) compared to baseline. Fasting glucose did not significantly improve in the health education group. There were no significant changes in blood pressure, weight, or insulin resistance in the MBSR group. Conclusions: In women with overweight or obesity, MBSR significantly reduces stress and may have beneficial effects on glucose. Future studies demonstrating long‐term cardiometabolic benefits of MBSR will be key for establishing MBSR as an effective tool in the management of obesity.